Die Schaffung eines Marktes : Preispolitik, Wettbewerb und der Handel mit Fernsehgeräten in der BRD und den USA, 1945-1985 - Teupe, Sebastian (Schriftenreihe zur Zeitschrift für Unternehmensgeschichte, 2016)
Did markets function differently in West Germany and the United States? This study in economic sociology examines this question by focusing specifically on the market for TV sets. It shows that social contexts decidedly shape market behavior on the part of manufacturers, dealers, and consumers. The study thus transcends the model of national "market cultures" to reveal changes in and similarities between consumer markets in the two societies